Time to evaluate: the students’ perspective of an online MA in CALL programme - Papadima-Sophocleous, Salomi; Giannikas, Christina N. (My University, 2019)
Despite the critical importance of Computer Assisted Language Learning (CALL) Teacher Education (CTE) programmes, L2 practitioners often report that there are not many such onsite/online programmes, and the ones that exist may not directly meet their specific needs. Moreover, there seems to be a lack of systematic evaluation studies of such courses. As a result, problems in such courses cannot be diagnosed, and they are left unresolved. This paper presents a study undertaken to evaluate an online Master’s of Arts (MA) in CALL programme in the Republic of Cyprus. The investigation was based on a conceptual multidimensional e-learning evaluation model rated by the students. Data were collected from 25 graduate students via an online anonymous survey. This focussed on the participants’ perceptions of the value of the following aspects: (1) their engagement; (2) the course and its organisation, teaching mode, and materials; (3) course strengths; (4) course aspects most helpful to learning; and (5) course aspects which were obstacles to learning. This paper discusses the findings and offers some first recommendations for further improvement to the MA in CALL programme.
Keywords: CALL teacher training programme evaluation; Students’ perspectives; Higher education; Evaluation research